A learner centered approach to online education - Harrell, Lisa (Emerald Publishing Limited : Information Age Publishing, 2013)
The purpose of this book is to serve as a guide for designing, developing, and teaching learner centered online courses and/or modules of instruction. This book will assist the reader in understanding the important factors in regards to online education. This book would also provide the foundational information, tools, and resource information needed to design, develop, and teach a learner centered online course or modules of instruction. This book would be a valuable resource for any educator interested in teaching online and for those who may already by teaching online. Educators in a variety of areas wishing to learn more about online teaching, course design, and course development could benefit from this book. This book could also serve as a text book for undergraduate and graduate courses related to online teaching, course design, and course development. This book could also serve as an administrative resource and guide for programs developing online courses and for faculty training and professional development purposes.